2014
DOI: 10.1063/1.4865253
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic magnetic fields in Vlasov-Maxwell equilibria

Abstract: Stationary solutions of Vlasov-Maxwell equations are obtained by exploiting the invariants of single particle motion leading to linear or nonlinear functional relations between current and vector potential. For a specific combination of invariants, it is shown that Vlasov-Maxwell equilibria have an associated Hamiltonian that exhibits chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Previous studies, such as Ghosh et al. (2014), have reported similar behaviour of magnetic fields in Vlasov–Maxwell equilibria. However, our analysis is more general than that of Ghosh et al.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Previous studies, such as Ghosh et al. (2014), have reported similar behaviour of magnetic fields in Vlasov–Maxwell equilibria. However, our analysis is more general than that of Ghosh et al.…”
Section: Introductionsupporting
confidence: 60%
“…Furthermore, chaotic behaviour is not unexpected in the context of kinetic equilibria. Previous studies, such as Ghosh et al (2014), have reported similar behaviour of magnetic fields in Vlasov-Maxwell equilibria. However, our analysis is more general than that of Ghosh et al (2014) because we prove the Hamiltonian nature of the equilibrium system for a wider class of distribution functions.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Research comprising dynamics of nonlinear magnetic fields in different systems including plasmas is an interesting field that has attracted numerous scientists in recent years. In this context, the phenomenon of occurrence of chaos in dynamical investigations of nonlinear magnetic fields in certain systems can be frequently encountered; this fact leads to chaotic magnetic fields in such systems with a predominance in plasmas [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This is because plasmas consist of different types of charged particles which generate electric and magnetic fields intrinsically and externally applied magnetic fields are required for their confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, occurrences of chaotic magnetic fields in tokamak plasma systems have been explored in [4,7,9] due to magnetic limiters. The phenomenon of charged particle energization in presence of regular as well as chaotic magnetic fields has been investigated by Samanta et al whereas occurrence of chaotic magnetic fields in Vlasov-Maxwell equilibria is discussed in [10]. Occurrence of chaotic magnetic fields in atmospheres has been discussed in [12] in context of reflections of various radiations.…”
Section: Introductionmentioning
confidence: 99%